CFD–DEM simulation of pneumatic conveying in a horizontal channel. (September 2019) - Zhao, Hemin; Zhao, Yongzhi
Highlights: A modified wall roughness model is introduced into the CFD–DEM approach. The DRW (Discrete Random Walk) model is introduced into the CFD–DEM approach. The improved CFD–DEM approach is used to study the dense-phase pneumatic conveying. Abstract: In this paper, the pneumatic conveying in a horizontal channel is simulated by the combined approach of computational fluid dynamics (CFD) and discrete element method (DEM). A modified wall roughness model and the Discrete Random Walk (DRW) model are introduced into the CFD–DEM approach to investigate the effect of the wall roughness and the random effect of the turbulence on particle dispersion respectively, and this combined approach is named as the improved CFD–DEM approach. The interaction between the particles and the fluid is calculated by both the one-way coupling method and the two-way coupling method. The accuracy of the improved CFD–DEM approach is validated by corresponding experiments from the literatures. By using the improved CFD–DEM approach, several dense channel gas–solid flows are simulated. The simulation results indicate that with the increase of mass loading rate, the particle agglomeration is more significant, and the trend of increasing the particle concentration near the upper and lower walls is more obvious. This research shows that the improved CFD–DEM approach developed in this work is an effective tool for studying the particle phase properties under both dilute and dense phase conditions.